2013
DOI: 10.1016/j.neulet.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Oral gabapentin treatment accentuates nerve and peripheral inflammatory responses following experimental nerve constriction in Wistar rats

Abstract: Gabapentin (GBP) is an anti-convulsive drug often used as analgesic to control neuropathic pain. This study aimed at evaluating whether oral GBP treatment could improve nerve inflammation response after sciatic nerve constriction in association with selected pain and motor spontaneous behavior assessments in Wistar rats. We evaluated nerve myeloperoxidase (MPO) and inflammatory cytokines on the 5th day post-injury, time in which nerve inflammation is ongoing. In addition, the role of GBP on carrageenan-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…So it can be deduced that gabapentinoids can interfere at different stages in the inflammatory cascade. In the literature, gabapentin and pregabalin are used for treatment of pain in a wide variety of dose ranges . We studied the effects of 20 mg/kg dose and found that it has a negative effect on wound healing.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…So it can be deduced that gabapentinoids can interfere at different stages in the inflammatory cascade. In the literature, gabapentin and pregabalin are used for treatment of pain in a wide variety of dose ranges . We studied the effects of 20 mg/kg dose and found that it has a negative effect on wound healing.…”
Section: Discussionmentioning
confidence: 44%
“…Gabapentin treatment increased peritoneal macrophage migration and carrageenan induced paw oedema, thus suggesting that gabapentin is a proinflammatory factor . The inflammation scores are higher in the gabapentin group in our study also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence strongly supports a role for inflammation in the progression of diabetic retinopathy and nephropathy (28,29), and cross-sectional and prospective studies have demonstrated elevated levels of circulating inflammatory mediators, including cytokines, chemokines, and acute-phase proteins, in the blood of T2D patients (30,31). In a rat nerve injury model, infiltration of inflammatory cells and an increase of cytokines is observed in the SCN (3234); however, little is known about the role of inflammation in DN in T1D and T2D models. In BTBR ob/ob mice, we observed significant elevation of IL-10, CCL11, CDCL1, and CXCL10 at 13 weeks, as well as an increasing trend for IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…84e87 Gabapentinoids reduce inflammatory mediators 69,73,78 and suppress dorsal horn activity 79,83 but contrasting effects have been shown. 84 There is some evidence to support pre-emptive treatment. 72,73,85 Gabapentin was effective in suppressing single motor unit response but not windup, indicating a peripheral mechanism of action.…”
Section: Effect On Inflammation and Postoperative Pain Modelsmentioning
confidence: 99%